Designing the Boundaries of the Firm: From “Make, Buy, or Ally” to the Dynamic Benefits of Vertical Architecture - Jacobides, Michael G.; Billinger, Stephan (Organization Science, 2006)
The concept of “vertical architecture” defines the scope of a firm and the extent to which it is open to final and intermediate markets; it describes the configurations of transactional choices along a firm’s value chain. A firm can make or buy inputs, and transfer outputs downstream or sell them. Permeable vertical architectures are partly integrated and partly open to the markets along a firm’s value chain. Increased permeability enables more effective use of resources and capacities, better matching of capabilities with market needs, and benchmarking to improve efficiency. Partial integration promotes a more dynamic, open innovation platform and enhances strategic capabilities by linking key parts of the value chain. This permeable vertical architecture, accompanied by appropriate transfer prices and incentive design, facilitates resource allocation and guides a firm’s growth process. Our longitudinal study of a major European manufacturer suggests that to understand how firm boundaries are set and what their impacts are, we need to complement the microanalytic focus on transactions with a systemic analysis at the level of the firm. It also shows how, over and above transactional alignment, decisions about boundaries and vertical architectures can transform a firm’s strategic and productive capabilities and prospects.